Carcass Percentage of Laying Ducks (Anas platyrhyncos) Supplemented by L-Arginine in Ration and Treated by L-Arginine In-Ovo Injection - Syahruddin, Syahruddin; Agustina, L.; Pakiding, W.; Malaka, R. (Tropical Animal Science Journal, 2019)
This study aimed to measure the effect of L-Arginine supplementation in the ration of laying duck and in-ovo injection of L-Arginine during egg incubation on breast muscle dimensions and carcass percentage of local duck. A total of 500 fertile eggs were obtained from laying ducks fed ration without supplementation of L-Arginine containing 1.04% digestible Arginine and 500 other fertile eggs were obtained from laying ducks fed ration supplemented with 0.25% L-Arginine containing 1.29% digestible Arginine. The eggs were subjected to 4 treatments with 5 replications. The treatments were: 1) eggs collected from laying ducks fed ration supplemented with 0% L-Arginine and in ovo injected with 0% L-Arginine during egg incubation as a control (P0); 2) eggs collected from laying ducks fed ration supplemented with 0% L-Arginine and in ovo injected with 1.5% L-Arginine during egg incubation (P1); 3) eggs collected from laying ducks fed ration supplemented with 0.25% L-Arginine and in ovo injected with 0% L-Arginine during egg incubation (P2); and 4) eggs collected from laying ducks fed ration supplemented with 0.25% L-Arginine and in ovo injected with 1.5% L-Arginine during egg incubation (P3). In-ovo injection of L-Arginine was performed on day 8th of incubation by injection of 1.5% L-Arginine into albumen using automatic syringe with a depth of 10 mm. The 180 day-olds hatched unsexed ducks were divided and moved into the pens according to the treatment groups. At the aged of 8 weeks, a male duck and a female duck from each experimental unit were measured for live weight and carcass weight, then the right Pectoralis major muscle sample was taken for histological analysis of myofibril. The results showed that supplementation of L-Arg in the ration of laying ducks and in-ovo injection of L-Arginine during egg incubation could increase muscle mass (number, diameter, and surface area) of the myofibril, live weight, and carcass percentage of offspring ducks compared to control offspring ducks. In conclusion, L-Arginine supplementation in the ration of laying ducks and in-ovo injections of L-Arginine into the eggs during incubation could increase breast muscle dimensions and carcass percentage of offspring local ducks.